ASSESSING ENGLISH TEACHING PROGRAM AT THE PRIMA SELECTA LAMPUNG: GRADUATES’ VOICE: mengukur efektifitas program pembelajaran bahasa inggris di Prima Selekta lampung - Mahmud, Mahmud; Suseno, Muchlas; Setiadi, Syamsi (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
This research aims to measure the effectiveness of English teaching program at the PRIMA Selecta Lampung based on student satisfaction responses. The subjects of this research are students who have completed English teaching Program at the PRIMA Selecta Lampung. The research instrument adopted from the Student Outcome Questionnaire (SOQ) which covers (1) Teaching, (2) Assessment (4) Generic skills, (4) learning experiences, and (5) Overall satisfaction. Data quantitative data were analyzed statistically by using a Likert scale and interpreted based on the four standard effectiveness criteria from Mardapi (2008) while the qualitative data were analyzed descriptively. The results of this research indicate that Teaching is categorized as Effective, Generic Skills is categorized as less effective, Learning Experience is categorized as quite effective, and Assessment is categorized as quite effective. Overall, learning English at the PRIMA Selecta Lampung educational institution is quite effective.